ANALISIS FUNGSIONAL SITUS SEWO, SOPPENG - nfn Hasanuddin (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
Megalithic culture is the biggest puzzle in pre-historic age. Living monument tradition or continuous megalithic tradition at Sewo site, for instance, is unable to explain its character or time it represented. This paper is attempting to analyze pre-historic elements and tradition which has no strict limitations. Etnoarchaeological approach is used to exploring ideas (mental template), site functions and social organization from megalithic supported community of Sewo, Soppeng.